Protective effects of paeoniflorin on cardiovascular diseases: A pharmacological and mechanistic overview - Li, Xiaoya; Sun, Changxin; Zhang, Jingyi; Hu, Lanqing; Yu, Zongliang; Zhang, Xiaonan; Wang, Zeping; Chen, Jiye; Wu, Min; Liu, Longtao (Frontiers in Pharmacology, 2023)
Background and ethnopharmacological relevance: The morbidity and mortality of cardiovascular diseases (CVDs) are among the highest of all diseases, necessitating the search for effective drugs and the improvement of prognosis for CVD patients. Paeoniflorin (5beta-[(Benzoyloxy)methyl] tetrahydro-5-hydroxy-2-methyl-2,5-methano-1H-3,4-dioxacyclobuta [cd] pentalen-1alpha (2H)-yl-beta-D-glucopyranoside, C23H28O11) is mostly derived from the plants of the family Paeoniaceae (a single genus family) and is known to possess multiple pharmacological properties in the treatment of CVDs, making it a promising agent for the protection of the cardiovascular system. Aim of the study: This review evaluates the pharmacological effects and potential mechanisms of paeoniflorin in the treatment of CVDs, with the aim of advancing its further development and application. Methods: Various relevant literatures were searched in PubMed, ScienceDirect, Google Scholar, and Web of Science. All eligible studies were analyzed and summarized in this review. Results: Paeoniflorin is a natural drug with great potential for development, which can protect the cardiovascular system by regulating glucose and lipid metabolism, exerting anti-inflammatory, anti-oxidative stress, and anti-arteriosclerotic activities, improving cardiac function and inhibiting cardiac remodeling. However, paeoniflorin was found to have low bioavailability, and its toxicology and safety must be further studied and analyzed, and clinical studies related to it must be carried out. Conclusion: Before paeoniflorin can be used as an effective therapeutic drug for CVDs, further in-depth experimental research, clinical trials, and structural modifications or development of new preparations are required.